1959
DOI: 10.1079/bjn19590003
|View full text |Cite
|
Sign up to set email alerts
|

The diet of sledge dogs

Abstract: The present activity in the Antarctic provided a stimulus for a study of the diet of sledge dogs. Observations made and results obtained in the Antarctic, together with cognate laboratory studies carried out in Britain, are here described. Experiments were made in Britain on dogs of various breeds, and in the Antarctic on huskies. The established sledging ration was found to be inadequate, so a product, pemmican, manufactured and supplied as blocks of I lb. to expeditions over the past 26 years was specially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1963
1963
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Dogs fed on lean seal meat passed only 2 % of the ingested nitrogen in their faeces, but dogs fed on pemmican and Nutrican passed 30% and 25 yo of the ingested I 966 nitrogen respectively. The high figure for nitrogen excretion for pemmican-fed dogs corresponds very closely to that of Taylor et al (1959) (33 %). One can only conclude that processing in some way renders the protein of the artificial diets less digestible.…”
Section: Nitrogen Excretionsupporting
confidence: 57%
See 3 more Smart Citations
“…Dogs fed on lean seal meat passed only 2 % of the ingested nitrogen in their faeces, but dogs fed on pemmican and Nutrican passed 30% and 25 yo of the ingested I 966 nitrogen respectively. The high figure for nitrogen excretion for pemmican-fed dogs corresponds very closely to that of Taylor et al (1959) (33 %). One can only conclude that processing in some way renders the protein of the artificial diets less digestible.…”
Section: Nitrogen Excretionsupporting
confidence: 57%
“…T h e figures of Taylor et al (1959) for pemmican-fed dogs are similar (72 %). Wyatt's (1963) figures for total excretion are rather lower, but he attributes this to coprophagy.…”
Section: Total Faecal Excretionmentioning
confidence: 74%
See 2 more Smart Citations
“…(0.45 kg) of Pemmican/dog/day yielding 2200 kcal. Taylor, Worden & Waterhouse (1959) showed that sledge dogs passed as much as 30 % of the protein content of the Pemmican diet in their faeces and devised an improved sledging ration Nutrican, yielding 2900 kcal/lb., which has been used since 1956 (Wyatt, 1962).…”
mentioning
confidence: 99%